Application of a new ultrasound criterion for the diagnosis of polycystic ovary syndrome - Giménez-Peralta, Iván; Lilue, Mariela; Mendoza, Nicolás; Tesarik, Jan; Mazheika, Marina (Frontiers in Endocrinology, 2022)
Objective: To define which ultrasound criteria could replace the classic Rotterdam criteria as the best indicator of the risk of developing endocrine-metabolic changes in PCOS women. Materials and methods: Multicentre cross-sectional study with 200 women with PCOS and one control group of 111 women without PCOS. The primary outcomes to be considered were the follicular count, hirsutism, total testosterone levels, free androgen index (FAI) and insulin sensitivity (HOMA-IR), the secondary outcome was the antimullerian hormone (AMH) level. Results: The main finding in this study points towards a different ultrasound criterion: twenty-three or more follicles of any size in at least one ovary, which is postulated as an alternative to the classic criterion described in the Rotterdam consensus. This criterion correlates better with the other two PCOS criteria and also identifies women at increased risk of hirsutism (Ferriman-Gallwey 6.08 ± 3.54 vs 4.44 ± 3.75, p<0.0001), total testosterone levels (2,24± 0,298 vs 1.42 ± 1,530, p= 0.0001); FAI (4.85 ± 0.83 vs 2.12 ± 1.93, p < 0.001) and insulin resistance (HOMA-IR 1,74 ± 0,182 vs 1,504 ± 0,230, p= 0.001) more accurately. Regarding AMH, large differences in their mean values were observed between groups (7.07 vs 4.846 ng / ml, p = 0.000). However, these differences depended on age. In conclusion, the ovarian ultrasound examination with 23 or more follicles of any size in any of the ovaries constitutes a powerful tool to accurately diagnose PCOS and to associate it with metabolic endocrine processes such as hyperandrogenism and insulin resistance